Developmental regulation of long-range neuroblast migration by Eph/ephrin signaling - Yeroshenko, Daria; de Silva, Chamalka; Burli, Anika; Bellizzi, Sarah; Singh, Vijender; Conover, Joanne (Frontiers in Neuroscience, 2025)
In the developing mouse anterior forebrain, the rostral migratory stream (RMS) supports continued proliferation and efficient transportation of large quantities of neuroblasts from the ventricular-subventricular (V-SVZ) stem cell niche to the olfactory bulb (OB). Astrocytes aid this migration by providing a glial network through which chains of fasciculated neuroblasts move. The largest receptor tyrosine kinase family, Eph receptors, and their ephrin ligands have been implicated in controlling neuroblast migration and astrocyte organization within this pathway. However, a clear understanding of the regulatory mechanisms underlying Eph/ephrin signaling remains elusive due, in part, to the complexity of heterogeneous expression patterns in both neuroblasts and astrocytes, as well as the cytoarchitectural changes that occur during postnatal development. To address this gap, we analyzed RMS cytoarchitecture together with transcriptomic and proteomic profiles at postnatal days P6, P12, and P60, and mapped Eph-ephrin interactions using predictive interaction models. Our data revealed temporally regulated, cell type-specific, receptor-ligand interactions, highlighting the prevalence and dynamic shifts of neuroblast-neuroblast, neuroblast-astrocyte, astrocyte-astrocyte interactions. Together, these findings established a framework that deconvoluted and characterized Eph and ephrin signaling as the RMS changed from a diffuse stream of migratory neuroblasts to a highly constricted pathway of neuroblast chains within astrocytic networks.